Calvin in context - Steinmetz, David Curtis (New York, N.Y. Oxford U.P., 1995)
Includes bibliographical references and index.
Keywords: Calvin, Jean, -- 1509-1564; Calvinism (theology) -- history; Reformation -- history; Reformed church -- doctrines -- history -- 16th century